Improving Islamic Religious Education Teachers’ Pedagogical Competence Through Educational Technology Training: A Case Study in Surakarta Madrasah - Sutrisno, Agus; Fatimah, Meti (Abjadia : International Journal of Education, 2025)
This study aims to describe the experiences of Islamic Religious Education teachers in implementing educational technology after participating in training. The research employed a descriptive qualitative approach, utilising data collection techniques that included observation, interviews, and documentation. The results indicate that educational technology training has a significant impact on improving the competency of Islamic Religious Education teachers. First, teachers become more skilled and confident in utilising digital media, such as interactive PowerPoint, Canva, Google Classroom, YouTube, Kahoot, and Google Forms, to present material in a varied and engaging way. Second, teachers are able to integrate technology into their lesson plans in a structured manner, resulting in more innovative and effective learning strategies. Third, the use of technology has been shown to increase student participation, foster creativity, and strengthen collaboration in learning activities. These findings indicate that educational technology training not only improves teachers' technical skills but also shifts the learning paradigm to become more modern, interactive, and student-centred.